Diagnostic performance of lactate dehydrogenase (LDH) isoenzymes levels for the severity of COVID-19 - KOCAKAYA, DERYA (My University, 2023)
Background: Lactate dehydrogenase (LDH) levels predict coronavirus disease 2019 (COVID-19) severity. We investigated LDH isoenzyme levels to identify the tissue responsible for serum LDH elevation in patients with COVID-19. Methods: Hospitalised COVID-19 patients with serum LDH levels exceeding the upper reference limit included. LDH isoenzymes were detected quantitatively on agarose gels. The radiological severity of lung involvement on computed tomography was scored as 0–5 for each lobe (total possible score, 0–25). Disease severity was determined using the World Health Organization (WHO) clinical progression scale. Results: In total, 111 patients (mean age, 59.96 ± 16.14), including 43 females (38.7%), were enrolled. The serum levels of total LDH and all five LDH isoenzymes were significantly higher in the severe group. The levels of all LDH isoenzymes excluding LDH5 positively correlated with the WHO score. LDH3 levels correlated with chest computed tomography findings (r2 = 0.267, p = 0.005). On multivariate analysis, LDH3 was an independent risk factor for the deterioration of COVID-19. Conclusions: LDH3 appears to be an independent risk factor for deterioration in patients with COVID-19. LDH elevation in patients with COVID-19 predominantly resulted from lung, liver and muscle damage. Keywords: Coronavirus, COVID-19, Lactate Dehydro - genase, LDH isoenzymes

Uvod: Nivoi laktat dehidrogenaze (LDH) predvi|aju ozbilj - nost bolesti korona virusa 2019 (COVID-19). Istra`ivali smo nivoe LDH izoenzima da bismo identifikovali tkivo odgovorno za povi{enje LDH u serumu kod pacijenata sa COVID-19. Metode: Uklju~eni su hospitalizovani pacijenti sa COVID-19 sa nivoom LDH u serumu koji prelazi gornju referentnu granicu. LDH izoenzimi su kvantitativno detektovani na agaroznim gelovima. Radiolo{ka te`ina zahvata plu}a na kompjuterizovanoj tomografiji ocenjena je sa 0–5 za svaki re`anj (ukupan mogu}i rezultat, 0–25). Te`ina bolesti je odre|ena kori{}enjem skale klini~ke progresije Svetske zdravstvene organizacije (SZO). Rezultati: Ukupno je uklju~eno 111 pacijenata (srednja starost 59,96 ± 16,14), uklju~uju}i 43 `ene (38,7%). Nivoi ukupnog LDH i svih pet LDH izoenzima u serumu su bili zna~ajno vi{i u te{koj grupi. Nivoi svih LDH izoenzima, isklju~uju}i LDH5, pozitivno su korelirali sa rezultatom SZO. Nivo bili su LDH3 u korelaciji sa nalazima kompjuterizovane tomografije grudnog ko{a (r2 = 0,267, p = 0,005). U multivarijantnoj analizi, LDH3 je bio nezavisni faktor rizika za pogor{anje COVID-19. Zaklju~ak: ^ini se da je LDH3 nezavisan faktor rizika za pogor{anje stanja kod pacijenata sa COVID-19. Povi{enje LDH kod pacijenata sa COVID-19 je uglavnom rezultat o{te}enja plu}a, jetre i mi{i}a. Klju~ne re~i: koronavirus, COVID-19, laktat dehidrogenaza, LDH izoenzimi
Dijagnosti^ki zna^aj nivoa izoenzima laktat dehidrogenaze (LDH) za procenu te@ine covid-19